Language Without Speech: Segregating Distinct Circuits in the Human Brain. (2nd August 2019) - Finkl, Theresa; Hahne, Anja; Friederici, Angela D; Gerber, Johannes; Mürbe, Dirk; Anwander, Alfred
Abstract: Language is a fundamental part of human cognition. The question of whether language is processed independently of speech, however, is still heavily discussed. The absence of speech in deaf signers offers the opportunity to disentangle language from speech in the human brain. Using probabilistic tractography, we compared brain structural connectivity of adult deaf signers who had learned sign language early in life to that of matched hearing controls. Quantitative comparison of the connectivity profiles revealed that the core language tracts did not differ between signers and controls, confirming that language is independent of speech. In contrast, pathways involved in the production and perception of speech displayed lower connectivity in deaf signers compared to hearing controls. These differences were located in tracts towards the left pre-supplementary motor area and the thalamus when seeding in Broca's area, and in ipsilateral parietal areas and the precuneus with seeds in left posterior temporal regions. Furthermore, the interhemispheric connectivity between the auditory cortices was lower in the deaf than in the hearing group, underlining the importance of the transcallosal connection for early auditory processes. The present results provide evidence for a functional segregation of the neural pathways for language and speech.